2021
DOI: 10.4103/1735-5362.319579
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of gallic acid on nicotine-induced testicular toxicity in mice

Abstract: Background and purpose: Nicotine is an alkaloid found in many nutrients and tobacco that can cause infertility in men. Gallic acid is a powerful antioxidant that possesses antimutagenic and anticancer activities. This study aimed to determine the potential protective effect of gallic acid against nicotine-induced testicular toxicity in male mice. Experimental approach: In this in vivo study, forty-eight mice were equally divided into eight gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The promising nutritive and health-related benefits of certain secondary metabolites present within CB fruits remain to be assessed. For example, gallic acid has been shown to be effective for the treatment of liquefied petroleum gas poisoning ( Akinmoladun et al, 2021 ), and intestinal parasites ( Bouaziz et al, 2021 ), and in smokers, it can also reverse the negative impacts of nicotine on male fertility ( Jalili et al, 2021 ). As CB fruits contain relatively high gallic acid levels (7.30 × 10 6 ), further research into the health-related benefits of this CB-derived compound is warranted.…”
Section: Future Challenges and Trendsmentioning
confidence: 99%
“…The promising nutritive and health-related benefits of certain secondary metabolites present within CB fruits remain to be assessed. For example, gallic acid has been shown to be effective for the treatment of liquefied petroleum gas poisoning ( Akinmoladun et al, 2021 ), and intestinal parasites ( Bouaziz et al, 2021 ), and in smokers, it can also reverse the negative impacts of nicotine on male fertility ( Jalili et al, 2021 ). As CB fruits contain relatively high gallic acid levels (7.30 × 10 6 ), further research into the health-related benefits of this CB-derived compound is warranted.…”
Section: Future Challenges and Trendsmentioning
confidence: 99%
“…The robust anti-inflammatory activity of GA could be used to treat a variety of inflammation-related diseases [15]. It is extensively discussed in the literature of this field [14][15][16][17][18][19]. Other bioactive compounds from vegetal sources have also been discussed and studied, claiming the same health benefits, and relating antibacterial, cardioprotective, anti-cancer, and antiinflammatory effects, as well as immune system stimulating and skin protective effects [11,20].…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine easily passes through the membrane of body cells and has the ability to react with some intracellular components such as tubulin protein in the cytoplasm of dividing cells such as germ cells. It has been found that the consumption of nicotine causes disruption in the spermatogenesis process; atrophy and damage to the testicles through induce oxidative stress and increase reactive oxygen radicals (ROS) production in mice ( Jalili et al ., 2021 ). The balance of the oxidant and antioxidant defense systems is essential for maintaining sperm functionality.…”
Section: Introductionmentioning
confidence: 99%